أثر التفوق التنظيمي في تحقيق التفوق التنافسي لشركة دراسة ميدانية لمؤسسة الدهن فرع –سوق اهراس- - (:unkn) unknown (My University, 2021)
The study aims to show the role of organizational excellence in achieving competitive superiority, by relying on the descriptive analytical approach, where the theoretical aspect was addressed to the independent variable organizational superiority and the dependent variable competitive superiority. The theoretical aspect was applied to the field reality in the National Oil Corporation - Ahras Market Unit - In order to achieve the objectives of the study, the spss program was used to analyze the questionnaires that were distributed to senior and middle management employees to prove the validity of the hypotheses that there is a significant linear relationship between organizational superiority and competitive superiority in Ahras Market Unit Foundation at a level of significance of 0.05; There is a statistically significant effect of organizational superiority on competitive superiority at the level of significance 0.05; there are significant differences between the mean of the answers of the study sample due to the variable of gender and academic qualification at the level of morale 0.05; it has been concluded that there is a positive effect relationship between the two variables, based on the results of the study that The institution under study applies the dimensions The study summarized a set of recommendations, the most important of which is the need to develop organizational structures and design new structures that are flexible to enable them to adapt to emergency environmental conditions. The necessity of paying attention to organizational excellence and reviewing its objectives and elements on an ongoing basis to enhance the positive aspects and address the negative aspects, as it is a variable that contributes to achieving competitive excellence. ............................................................. الدراسة تهدف الى تبيان دور التفوق التنظيمي في تحقيق التفوق التنافسي ، وذلك بالاعتماد على المنهج الوصفي التحليلي، حيث تم التطرق في الجانب النظري الى المتغير المستقل التفوق التنظيمي والمتغير التابع التفوق التنافسي، وتم تطبيق الجانب النظري على الواعع الميداي في المؤسسة الوطنية للدهن –وحدة سوق اهراس-من اجل تحقيق اهداف الدراسة ، بحيث تم استخدام برنامج spss لتحليل الاستبيانات التي وزعت على موظفي الادارة العليا و الادارة الوسطى لاثبات صحة الفرضيات والتي مفادها ت وجد علاعة خطية معنوية بين التفوق التنظيمي و التفوق التنافسي في مؤسسة وحدة سوق اهراس عند مستوى معنوية 0.5 .؛يوجد تاثير ذات دلالة احصائية للتفوق التنظبمي على التفوق التنافسي عند مستوى معنوية 0.5 .؛توجد اختلافات معنوية بين متوسطي اجابات عينة الدراسة تعزى لمتغير الجنس و المؤهل العلمي عند ؛. مستوى معنوية 0.5 وعد تم التوصل الى وجود علاعة تاثير ايجابية بين المتغيرين وذلك بناءا على نتائج الدراسة مفادها ان المؤسسة محل الدراسة تطبق ابعاد التفوق التنظيمي من اجل تحقيق التفوق التنافسي لضمان بقاءها و استمراريتها وولاء زبائنها وموظفيها . و عد لخصت الدراسة إلى مجموعة من التوصيات من أهمها ضرورة تطوير الهياكل التنظيمية وتصميم هياكل جديدة تتسم بالمرونة لتمكنها من التكيف مع الظروف البيئية الطارئة ؛ضرورة الاهتمام بالتفوق التنظيمي ومراجعة اهدافه وعناصره بشكل مستمر لتعزيز جوانب الايجابية ومعالجة الجوانب السلبية ،كونه متغير يساهم في تحقيق التفوق التنافسي ؛تشجيع انشاء وحدات بحث وتطوير للاستممار في الجانب الابداعي 0.5
فاطمة لعوادي
شيماء هميسي